Penyelesaian Isykāl Hadis Mayat Diazab karena Ratapan - Arfan; Afni A., Nur (JAWAMI'UL KALIM: Jurnal Kajian Hadis, 2023)
This research discusses the isykāl hadith about corps being punished by wailing along with the scholars' resolution of this isykāl. This research uses a descriptive method through a content analysis approach, through literature review, both books written by classical scholars and scientific books and articles compiled by contemporary researchers, as well as other relevant sources. The hadiths which are the object of study are only taken from al-Ṣaḥīḥain or one of the two so that the author no longer criticizes the sanad but instead goes directly to the analysis of the existing matan-matan. Next, all the information obtained during the research will be analyzed to draw the conclusions. The results of this research found that isykāl in the hadith of corpses being tortured because of wailing is a hadith which is considered to be contrary to the verse of the Al-Qur’an, namely "It is not for a sinful person to bear the sins of others." (Q.S. al-An'ām/6: 164). The scholars took a number of ways to resolve the isykāl. There are at least six solutions offered by scholars. The author is more inclined to the opinion that ta'żīb (torture) in this hadith means torture, not 'iqāb (punishment), namely a corpse tortured by the wailing of his family, but that is not a punishment. Because, it is impossible for someone to be punished because of another person's actions as in the verse above. This interpretation is closer to the original law of generality and absoluteness of hadith than other interpretations so that according to existing rules it is closer to the truth.